Pedagogical Opportunities of Wrestling Sports in the Formation of a Sense of National Pride in Students - M.Tashbaeva (Genius Publishing Group, 2022)
The article explores the use of physical education classes and extracurricular activities in wrestling to form a sense of national pride in students. Wrestling is also considered as one of the key factors in educating a harmoniously developed generation
Keywords: Harmoniously developed generation; pride; sense of national pride; personality